The Diagnosis and Treatment of Streptococcal Pharyngitis - Parsons, W.D. (1987)
To prevent rheumatic fever (RF) most authorities have recommended that treatment of pharyngitis be guided routinely by throat culture results. The recognition of a dramatic decline in the incidence of RF has rekindled the debate about the place of throat culture. Using clinical judgement alone, most practitioners would treat four or five patients for each culture positive. Although it is possible to use algorithms to select low- and high-risk groups for whom culture may not be necessary, a specific diagnosis must still be sought in the majority of patients. Diagnostic kits for rapid detection of group A streptococus facilitates this approach.